Análisis del perfil socioeconómico y ambiental de la comuna las huacas, archipiélago de jambelí - Sanchez Sarango, Domenica Belen (Machala : Universidad Técnica de Machala, 2021)
This article presents an overview of the socioeconomic and environmental profile of the artisanal capture of conch (Anadara tuberculosa) in the Las Huacas commune located in the Jambelí archipelago of the El Oro province of Ecuador. The objective of the research is to analyze the socioeconomic and environmental profile of the commune based on the indicators of social, economic and environmental dimension. This research obeyed a non-experimental, field and cross-sectional design, which was carried out using a technical sheet of questionnaires applied to the associates. the population was dominated by the male gender (119) over the female (19); Relatively, it represents (14%) the participation of women among the associates. The Chi-square test was applied to determine significance (p <0.05) in the indicators reason for undertaking / need or opportunity and Schooling / average income. It is concluded that there is a dependency relationship between the variables need and opportunity to undertake, while there is no statistical association between the categorical variables level of formal education and income. A relevant data could be evidenced in the environmental indicator that 67.15% of the associates established that they always apply environmental care in the shellfish activity, and 53.63% revealed that they always carry out improvement activities to clean up the environment.
El presente artículo presenta un panorama general sobre el perfil socioeconómico y ambiental de la captura artesanal de conchas (Anadara tuberculosa) en la comuna Las Huacas ubicada en el archipiélago de Jambelí de la provincia de El Oro de Ecuador. El objetivo de la investigación es analizar el perfil socioeconómico y ambiental de la comuna en función de los indicadores de dimensión social, económica y ambiental. Esta investigación obedeció a un diseño no experimental, de campo y transversal, la cual se realizó mediante una ficha técnica de cuestionarios aplicados a los asociados. la población fue dominada por el género masculino (119) sobre el femenino (19); de forma relativa representa un (14%) la participación de la mujer entre los asociados. Se aplicó la prueba de Chi-cuadrado para determinar significancia (α<0.05) en los indicadores razón de emprender/necesidad u oportunidad y Escolaridad/ingresos promedio. Se concluye que existe una relación de dependencia entre las variables necesidad y oportunidad de emprender, mientras que no existe asociación estadística entre las variables categóricas nivel de instrucción formal e ingresos económicos. Un dato relevante se pudo evidenciar en el indicador ambiental que el 67,15% de los asociados establecieron que siempre aplican cuidados ambientales en la actividad conchera, y el 53,63% revelaron que siempre realizan actividades de mejora para sanear el medio ambiente.
Keywords: PRODUCCIÓN; ACTIVIDAD; CONCHERA; CONCHEROS